2018
DOI: 10.1038/s41598-018-19410-1
|View full text |Cite
|
Sign up to set email alerts
|

Restrained management of copper level enhances the antineoplastic activity of imatinib in vitro and in vivo

Abstract: The present study was designed to investigate if elevated copper level can be targeted to enhance the efficacy of a significant anticancer drug, imatinib (ITB). The antineoplastic activity of this drug was assessed in the HepG2, HEK-293, MCF-7 and MDA-MD-231 cells targeting elevated copper level as their common drug target. The cell lines were treated with the different doses of copper chloride (Cu II) and disulfiram (DSF) alone as well as in their combinations with the drug for 24 h in standard culture medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 55 publications
1
28
1
Order By: Relevance
“…Clinicaltrials.gov Identifier NCT02963051 study completion date: August 2020] and Phase II Trial of Disulfiram With Copper in Metastatic Breast Cancer ClinicalTrials.gov Identifier NCT03323346; study completion date September 2020]. Since KRAS mutation and c-Myc amplification cooperate with KRAS in tumourigenesis [3537], this report used cell lines differing in BRAF, KRAS and C-MYC status to gain insight into their modulation of response to Cu chelators. We found that 2.5-μM TTM or low 0.1-μM DSF did not suppress growth and metabolic activity in two wt p53 human melanoma cells harbouring KRAS mutation and high c-MYC (C8161) or BRAF mutation and low c-MYC (A375) (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicaltrials.gov Identifier NCT02963051 study completion date: August 2020] and Phase II Trial of Disulfiram With Copper in Metastatic Breast Cancer ClinicalTrials.gov Identifier NCT03323346; study completion date September 2020]. Since KRAS mutation and c-Myc amplification cooperate with KRAS in tumourigenesis [3537], this report used cell lines differing in BRAF, KRAS and C-MYC status to gain insight into their modulation of response to Cu chelators. We found that 2.5-μM TTM or low 0.1-μM DSF did not suppress growth and metabolic activity in two wt p53 human melanoma cells harbouring KRAS mutation and high c-MYC (C8161) or BRAF mutation and low c-MYC (A375) (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although exogenous Cu supplementation has been widely used by others to augment the efficacy of TTM [3, 1215] and DSF [18, 20, 21], we reported that DSF was much more effective than TTM as an anticancer agent even without Cu supplementation to avoid collateral Cu toxicity [26]. Another study investigating if elevated copper enhances the efficacy of the anticancer drug, imatinib (ITB), also showed that DSF was more effective than high Cu (II) as an adjuvant to ITB [37], confirming our belief that restrained manipulation of copper level in tumour may lead to a more selectively targeted killing of tumour cells and diminished collateral toxicity. DSF also showed greater efficacy against SW-620 and Caco-2 CRC cells, compared to the relatively greater resistance to DSF ± OxPt in BRAF (V600E)/ p53 mut HT-29 CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…This action of RF firstly absorbs the toxic shock of PB in a dose-dependent manner by elevating the activity of major antioxidant enzymes and GSH. In addition, RF can bring down the oxidative stress level and proportionate the ATP level (by enhancing intestinal mucosa absorption and boosting metabolism) that helps the partially damaged cells to undergo a normal cell cycle; at the same time, such concurrent conditions also trigger programmed cell death in the damaged cells [25,27,29,38,54,55]. The study clearly shows that PB triggers more necrotic and inflammatory features besides apoptosis.…”
mentioning
confidence: 85%
“…The strong connection between copper and tumor development, as well as metastization has encouraged scientists to design and synthesize new copper-complexing agents to be used in chemotherapy with lower side effects (79,91). The copperbinding compounds used as anticancer agents are divided in two groups: copper chelators, which sequester copper ions from cells, and copper ionophores, which vehicle copper inside cells increasing its intracellular levels and priming cytotoxic effects through multiple pathways (116,117). The copper complexing species tetrathiomolybdate (TTM), disulfiram, and clioquinol have been employed in clinical trials, but only TTM has given the most promising results (117).…”
Section: Opportunities To Improve Cancer Therapymentioning
confidence: 99%